Longitudinal and radial permeability analysis of additively manufactured porous scaffolds: Effect of pore shape and porosity. (15th May 2017) - Montazerian, H.; Zhianmanesh, M.; Davoodi, E.; Milani, A.S.; Hoorfar, M.
Abstract: While in practice cell ingrowth in scaffolds mostly occurs radially, the recent literature has mainly emphasized on modeling permeability under unidirectional flows. In this article, we attempt to introduce the radial flow direction as another important factor for scaffold internal architecture design, and thereby show its trade-off with the conventionally studied longitudinal permeability. To this end, a set of computational models is developed for different lattice and triply periodic minimal surface-based geometries to predict the corresponding structure-property relationships with respect to different porosity levels. Also, permeability is experimentally investigated for different values of porosity through 3D-printing of the selected critical structures as identified by the numerical models; namely Hexagonal and Rhombic Dodecahedron. Relative to the longitudinal permeability, the normalized radial permeability is shown to change by − 51.2% and 39.4% for Hexagonal and Rhombic Dodecahedron, respectively, implying the necessity of including radial permeability as a more realistic computational tool for the design of scaffold pore architecture. Moreover, the permeability-porosity relationship was developed through both the power law as well as the Kozeny-Carman models and the effects of experimental conditions on the permeability values were discussed. Graphical abstract: Highlights: Radial permeability was for the first time characterized for scaffold structures. Different porosities of lattice and TPMS based geometries were numerically analyzed. Experimental permeability was evaluated for scaffolds with critical permeability. Permeability-porosity relations were found by scaling-law and Kozeny-Carman models. The effect of fluid height on permeability was analyzed experimentally.